Trauma Healing through the Upah-Upah Songgot Tradition: A Case Study of an Indigenous Community in Indonesia - Alawiyah, Winda; Ritonga, Hasnun Jauhari (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The upah-upah sanggot tradition is one of the cultural heritages used for the trauma healing process in indigenous communities in Indonesia. This research aims to find out the upah-upah songgot in the Batak toba custom as a post-disaster trauma healing effort carried out by one of the communities in Indonesia. This research uses qualitative methods, using primary and secondary sources. Data collection techniques were carried out by observation and interviews. Interview questions were analyzed using the Miles and Huberman approach and data validity was carried out using data triangulation. The research findings show that the upah-upah songgot custom is carried out in order to restore the spirit of the soul of individuals who feel threatened. Where they the family comes suddenly without notice by bringing food in the form of dekke (carp) arsik and rice to entertain families who experience calamity or illness. The process of implementing wage-upah is to gather together with the traumatized person who will usually be presented in the middle of the family who comes then disurduk (given) a dekke na niarsik (cook arsik) which has been arranged in a drained plate containing rice and Rudang, the hula-hula takes a handful of rice to put on the head of the sick and pray to the almighty to restore the spirit of life and healing. Giving a piece of ulos or sarong cloth that is placed behind the sick or the afflicted. After being given ulos, then eat together as well as pray together. Upah-upah songgot in the Toba Batak custom as a post-disaster trauma healing effort according to Batak culture is very effective in providing a spirit of life in obtaining healing. Upah-upah songgot in the Toba Batak custom as a trauma healing effort to be more successful requires the support of professional assistance in the sense that experts are assisted by psychiatrists or counselors.